FRAMING ECONOMIC STABILITY THROUGH LANGUAGE: A CRITICAL DISCOURSE ANALYSIS OF REDENOMINATION NEWS COVERAGE - Muhammad Fahri Jaya Sudding; Surya Anantatama Sembiring; Musdalifah; Citra Dwi Safitri (Program Studi Pendidikan Bahasa Inggris, 2025)
This study examines how Indonesian online news constructs the discourse of rupiah redenomination by analysing linguistic patterns, discursive structures, and ideological representations embedded within financial reporting. Using Norman Fairclough’s Critical Discourse Analysis (CDA), the article “Pemerintah Kembali Hidupkan Wacana Redenominasi Rupiah, Ekonomi Peringatkan Risiko Inflasi” was analysed across five levels: textual analysis, discursive practice, social practice, integrated interpretation, and explanatory critique. The findings indicate a discursive tension between government ambition to advance redenomination as a formal policy initiative and economists’ cautionary framing that emphasises risks of inflation, unstable exchange rates, high implementation costs, and uneven public readiness. The news text privileges technocratic voices and constructs redenomination as a potentially destabilising policy rather than a symbol of economic modernisation. This study concludes that online media play a critical role in shaping public perception by foregrounding expert skepticism and reproducing ideologies of fiscal prudence, market stability, and technocratic authority.